A COUNCIL ON ACCOUNTING RESEARCH. - Greer, Howard C. (The Accounting Review, 1932)
Abstract This article presents the need for a research program in accountancy. A longer-range objective is the application of research findings to actual accounting situations, in the hope that they may be helpful in establishing better standards for both accounting training and accounting practice. From suggestions submitted by the accountants consulted in this connection it is evident that the word research must be taken in a broad sense to cover the activities proposed. The task is not one of merely collecting facts, or even of suggesting interpretations and applications of such facts. Many of the problems which are most in need of solution call for a coordination and rationalization of existing current thinking and practice in respect to various aspects of accounting. Thus it seems that a research program in accountancy must include not simply studies in the theoretical and economic aspects of accountancy but also in the legal and social aspects of its practice. The word practice, too, is here used in its broadest sense, to include not merely the professional activities of public accountants but also the duties and responsibilities of accountants at work in the service of government and of private business.